2018
DOI: 10.1152/physiol.00022.2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physiology of Nociception and Pain

Abstract: The study of diverse animal groups allows us to discern the evolution of the neurobiology of nociception. Nociception functions as an important alarm system alerting the individual to potential and actual tissue damage. All animals possess nociceptors, and, in some animal groups, it has been demonstrated that there are consistent physiological mechanisms underpinning the nociceptive system. This review considers the comparative biology of nociception and pain from an evolutionary perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 152 publications
1
107
0
12
Order By: Relevance
“…In fact, there are likely to be substantial differences in fish sensory systems compared with a terrestrial animal due to differing ecological and evolutionary pressures [81]. The term Umwelt was coined by Jakob von Uexküll in 1909 and refers to the sensory world of an animal-i.e.…”
Section: Sensory Worldsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are likely to be substantial differences in fish sensory systems compared with a terrestrial animal due to differing ecological and evolutionary pressures [81]. The term Umwelt was coined by Jakob von Uexküll in 1909 and refers to the sensory world of an animal-i.e.…”
Section: Sensory Worldsmentioning
confidence: 99%
“…The aquatic environment influences basic perception and adaptation to damage in fishes: for example, they cannot fall because of buoyancy in the water column and this prevents injury due to gravity; noxious chemicals entering the aquatic environment may be diluted and thus pose a lower risk; and major shifts in temperature are less common compared with terrestrial environments. This could mean fishes experience less risk of damage than terrestrial animals, and it may be reflected in their nociceptive system [81]. In fact, although receptors for damaging stimuli have been found in all fish groups, and fishes possess neuroanatomical pathways comparable to those found in other vertebrate groups, there are interesting differences that reveal adaptions to evolutionary pressures: for example, rainbow trout nociceptors are not activated in low temperatures, because they live in cold water [91], but they are more sensitive to mechanical stimuli than mammals, probably because their skin is more fragile, and to heat, probably because they live in temperatures usually not above to 25 C[ 9 2 ] .T h eC h a m e l e o nc i c h l i d( Australoheros facetus), on the other hand, is far more tolerant to heat exposure, which can also be explained by its broad ecological distribution [93].…”
Section: Nociceptionmentioning
confidence: 99%
“…Nociceptors have been identified in non‐human mammals and other vertebrate groups such as amphibian, reptilian and avian species but can also be found in invertebrates (Sneddon et al ., ; Sneddon, , ). Empirical studies in fishes have also confirmed the presence of nociceptors, demonstrating their properties are very similar to those found in humans and other mammals (Ashley et al ., , ; Mettam et al ., ; Sneddon, , , ).…”
Section: Do Fishes Experience Pain?mentioning
confidence: 99%
“…Nociceptors have been identified in non‐human mammals and other vertebrate groups such as amphibian, reptilian and avian species but can also be found in invertebrates (Sneddon et al ., ; Sneddon, , ). Empirical studies in fishes have also confirmed the presence of nociceptors, demonstrating their properties are very similar to those found in humans and other mammals (Ashley et al ., , ; Mettam et al ., ; Sneddon, , , ). Studies in fishes have demonstrated changes in brain activity during noxious stimuli (Dunlop & Laming, ; Nordgreen et al ., ; Reilly et al ., ; Sneddon, ) and recorded adverse changes in behaviour and physiology during noxious treatments (Dunlop et al ., ; Maximino, ; Mettam et al ., ; Reilly et al ., ; Roques et al ., ; Sneddon, ; Sneddon et al ., , ; White et al ., ) all of which can be prevented by analgesics known to be effective in relieving pain in mammals (Lopez‐Luna et al ., , , , ; Mettam et al ., ; Newby et al ., ; Nordgreen et al ., ; Schroeder & Sneddon, ; Sneddon, , ; Taylor et al ., ).…”
Section: Do Fishes Experience Pain?mentioning
confidence: 99%
“…Throughout this paper, we focus on sensation, rather than perception. Details on the pain pathway can be found in multiple review papers [31,50,1,54,57].…”
Section: The Neuroscience Of Pain Sensationmentioning
confidence: 99%